Oxidation-Reduction Potential (ORP) during microbial transformation processes under aerobic, anoxic and anaerobic conditions / Hasnita Ahmad - Ahmad, Hasnita (2004)
The sewer is an integral part of the urban wastewater system. The sewer can also acts as a reactor, where the quality of the wastewater is affected by microbial changes during the transportation of the wastewater in the sewer. However, due to the lack of fundamental knowledge in oxidation-reduction potential (ORP) in bulk water phases under aerobic, anoxic and anaerobic conditions, the efforts towards modeling and design of sewer network incorporating the processes dimension is being restrained. The purposes of this study are to establish the change in ORP during microbial transformation processes in the bulk water phase under sewer condition and to establish the range of ORP under aerobic, anoxic and anaerobic condition s. This study is based on experimental works on microbial transformation processes in the bulk water phase of municipal wastewater. Test on 7 different municipal wastewater samples taken from the inlet of wastewater treatment plant (WWTP) at Mawar College and a manhole, near the Civil Engineering Laboratory were conducted. Two types of reactors were used in this study. The first reactor, subjected to aerobic conditions was used to determine the amount of substrate utilized by analyzing the OUR curve. The second reactor, subjec ted to aerobic, anoxic and anaerobic conditions was used to measure the ORP value and to determine the amount of dissolved oxygen, nitrate/nitrite and sulfate used during the aerobic, anoxic and anaerobic condition s. KEYWORDS Microbial transformation processes; aerobic, anoxic and anaerobic conditions, in-sewer processes, oxidation-reduction potential, initial COD-fractions, nitrate, nitrite, sulfate, oxygen utiIization rate.